Battery and electric device

By combining and adjusting the mass percentage of the first positive electrode active material and the second positive electrode active material in the lithium battery, the problem of the lithium battery with the charging rate tolerance boundary between the low SOC and high SOC intervals is solved, and the fast charging and cycling performance is improved.

CN116759568BActive Publication Date: 2025-01-14CONTEMPORARY AMPEREX TECHNOLOGY CO LTD

Patent Information

Application Number
CN202310229296.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-10
Publication Date
2025-01-14
Estimated Expiration
2043-03-10

AI Technical Summary

Technical Problem

The existing lithium batteries have narrow charging rate tolerance boundary in the low SOC interval, which affects fast charging performance, and the high SOC interval charge rate tolerance boundary deteriorates, resulting in poor circulation performance.

Method used

By combining the first positive electrode active material and the second positive electrode active material and limiting its mass percentage range, the proportion of the low SOC interval charging capacity less than 3.7V in the total charging capacity, and the low SOC interval charging rate tolerance boundary is improved. At the same time, the proportion of high SOC interval charging capacity in the total charging capacity is maintained, and the deterioration of the high SOC interval charging rate tolerance boundary is alleviated.

Benefits of technology

The fast charging and cycling performance of lithium batteries is improved, and more suitable low SOC and high SOC interval charging rate tolerance boundaries are obtained to ensure the smooth progress of the charging process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116759568B_ABST
    Figure CN116759568B_ABST
Patent Text Reader

Abstract

The present application provides a battery and an electric device, wherein the battery comprises a positive electrode plate, the positive electrode plate comprises a first positive electrode active material and a second positive electrode active material; the first positive electrode active material comprises a compound Li a Ni b Co c M1 d M2 e O f E g The second positive electrode active material includes a compound Li x H y Mn 1‑z Q z P 1‑m G m O 4‑n D n , and meet: #imgabs0#
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the technical field of lithium batteries, and particularly to a battery and an electrical device. Background Art

[0002] In recent years, with the increasingly wide application range of secondary batteries, secondary batteries are widely used in energy storage power systems such as hydraulic, thermal, wind, and solar power stations, as well as in multiple fields such as power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, and aerospace. Due to the great development of secondary batteries, higher requirements are put forward for their cycle performance, charging speed, service life, etc. Summary of the Invention

[0003] This application is made in view of the above problems, and its purpose is to provide a battery and an electrical device, which improve the fast charging performance and cycle performance of the battery.

[0004] To achieve the above object, a first aspect of this application provides a battery, including a positive electrode plate, and the positive electrode plate includes a first positive electrode active material and a second positive electrode active material; wherein,

[0005] The first positive electrode active material includes the compound Li a Ni b Co c M1 d M2 e O f E g ; wherein,

[0006] M1 includes one or two elements of Mn and Al;

[0007] M2 includes one or more elements of Zr, Zn, Cu, Cr, Mg, Fe, V, Ti, Sr, Sb, Y, W, and Nb;

[0008] E includes one or more elements of N, F, S, and Cl;

[0009] 0.75 ≤ a ≤ 1.2; 0 < b < 1; 0 < c < 1; 0 < d < 1; 0 ≤ e ≤ 0.2; 1 ≤ f ≤ 2.5, 0 ≤ g ≤ 1, and f + g ≤ 3;

[0010] The second positive electrode active material includes the compound Li x H y Mn 1-z Q z P 1-m G m O 4-n D n , wherein,

[0011] H includes one or more elements selected from Zn, Al, Na, K, Mg, Nb, Mo and W;

[0012] Q comprises one or more elements selected from Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ni, Co, Ga, Sn, Sb, Nb and Ge;

[0013] G includes one or more elements selected from B, Si, N, S, F, Cl and Br;

[0014] D comprises one or more elements selected from S, F, Cl and Br;

[0015] x is 0.9 to 1.1; y is 0 to 0.1; z is 0.001 to 0.9; m is 0 to 0.1; n is 0 to 0.1;

[0016] In addition, the battery meets the following requirements:

[0017]

[0018] in,

[0019] A represents the mass percentage of the second positive electrode active material in the two positive electrode active materials;

[0020] B represents the proportion of the charging capacity of the second positive electrode active material less than 3.7V in the entire charging capacity measured by the single particle microelectrode method;

[0021] C represents the proportion of the battery's charging capacity less than 3.7V in the total charging capacity;

[0022] R represents the resistance of the positive electrode at 25°C, in Ω.

[0023] Therefore, the present application defines a combination of a first positive electrode active material and a second positive electrode active material. Between 0.1 and 0.75, improves the battery's low SOC less than 3.7V

[0024] The proportion of interval charging capacity in the total charging capacity improves the tolerance boundary of the low SOC interval charging rate, while maintaining the proportion of high SOC interval charging capacity in the total charging capacity, alleviating the deterioration of the high SOC interval charging rate tolerance boundary, thereby improving the battery's fast charging performance and improving the battery's cycle performance.

[0025] In any embodiment,

[0026] Optionally,

[0027] Thus, more suitable charging rate tolerance boundaries for the low SOC range and the high SOC range can be obtained, thereby further improving the fast charging performance and / or cycle performance of the battery.

[0028] In any embodiment, A is from 0.1 to 0.5, optionally from 0.1 to 0.3, more optionally from 0.2 to 0.3; and / or,

[0029] B is from 0.4 to 0.6, optionally from 0.5 to 0.6; and / or,

[0030] C is from 0.05 to 0.23, optionally from 0.09 to 0.16; and / or,

[0031] 0 < R < 1, optionally from 0.1 to 0.6, more optionally from 0.2 to 0.4.

[0032] A, B, and C within the above ranges can further improve the charging rate tolerance boundary in the low SOC range, while making the charging rate tolerance boundary in the high SOC range more suitable, thereby further improving the fast charging performance and / or cycle performance of the battery;

[0033] R within the above range can obtain a lower overpotential, which is beneficial to improving the rate performance of the battery and making the charging process proceed smoothly.

[0034] In any embodiment, in the second positive electrode active material, Q includes one or more elements of Fe, Ti, V, Ni, Co, and Mg; and / or,

[0035] G includes one or more elements of B, Si, N, and S; and / or,

[0036] x is from 0.977 to 1; and / or,

[0037] y is from 0 to 0.001; and / or,

[0038] z is from 0.1 to 0.9 or from 0.001 to 0.6, optionally from 0.3 to 0.7; and / or,

[0039] m is from 0 to 0.001 or from 0.001 to 0.1; and / or,

[0040] n is from 0 to 0.001 or from 0.001 to 0.1.

[0041] Thus, by using a second positive electrode active material including the above-mentioned Q and G elements, the proportion of the battery's charging capacity in the low SOC range of less than 3.7V in the total charging capacity can be further increased, and the charging rate tolerance boundary in the low SOC range can be further improved. At the same time, the proportion of the charging capacity in the high SOC range in the total charging capacity can be maintained, and the deterioration of the charging rate tolerance boundary in the high SOC range can be alleviated, thereby further improving the battery's fast charging performance and / or cycle performance.

[0042] In any embodiment, in the first positive electrode active material, a is 0.9 to 1.1; and / or,

[0043] d is from 0.003 to 0.4; and / or,

[0044] b is 30% to 99.5%, optionally 50% to 99%, more preferably 55% to 88%; and / or,

[0045] c is 0.2% to 52%, optionally 0.5% to 49.5%, and more optionally 5% to 35%.

[0046] The Ni content within the above range can improve the fast charging performance and / or cycle performance of the battery.

[0047] The Co content within the above range can improve the fast charging performance and / or cycle performance of the battery.

[0048] In any embodiment, the first cathode material is a single crystal or a quasi-single crystal material and satisfies:

[0049] D of single crystal particles or single crystal-like particles v 50 The particle size is 1.5 to 4.5 μm, optionally 2 to 4.1 μm; and / or,

[0050] D of single crystal particles or single crystal-like particles v 99 particle size ≤ 18 μm, optionally 6.4 to 17.5 μm, more preferably 6.5 to 13.5 μm; and / or,

[0051] The BET specific surface area of ​​the first positive electrode active material is 0.42 to 1.2 m 2 / g, optional 0.5 to 1m 2 / g.

[0052] When the first positive electrode active material is a single crystal or a quasi-single crystal material, the above range of D v 50 particle size, D v 99 particle size and BET specific surface area are beneficial to increase the active sites of positive electrode active materials, improve the fast charging performance and power of the battery, help reduce the side reactions of positive electrode active materials, and improve the cycle performance of the battery.

[0053] In any embodiment, the first positive electrode active material is a polycrystalline material and satisfies:

[0054] The secondary particles have a Dv50 particle size of 6 to 14 μm, optionally 7 to 13 μm; and / or,

[0055] The Dv99 particle size of the secondary particles is <30 μm, optionally 14.2 to 28.8 μm, more preferably 15.4 to 26.7 μm; and / or,

[0056] The primary particles have a particle size of 50 to 800 nm, optionally 50 to 600 nm; and / or,

[0057] The BET specific surface area of ​​the first positive electrode active material is 0.8 to 1.2 m 2 / g, optional 0.8 to 1.1m 2 / g.

[0058] When the first positive electrode active material is a polycrystalline material, the secondary particles D in the above range v 50 particle size, secondary particle D v 99 particle size, primary particle size, and BET specific surface area are beneficial to increasing the active sites of the positive electrode active material, improving the fast charging performance and power of the battery, helping to reduce the side reactions of the positive electrode active material, and improving the cycle performance of the battery.

[0059] In any embodiment, the second positive electrode active material is a single crystal or a quasi-single crystal material and satisfies:

[0060] D of single crystal particles or quasi-single crystal particles v 50 The particle size is 0.2 to 1.6 μm, and optionally 0.25 to 1.49 μm; and / or,

[0061] D of single crystal particles or quasi-single crystal particles v 99 particle size is 5.2 to 33.8 μm, optionally 6.1 to 25.7 μm; and / or,

[0062] The BET specific surface area of ​​the second positive electrode active material is 11.3 to 14.1 m 2 / g, optional 12 to 13.7m 2 / g.

[0063] When the second positive electrode active material is a single crystal or a quasi-single crystal material, the above range of D v 50 particle size, D v 99 particle size and BET specific surface area are beneficial to increase the active sites of positive electrode active materials, improve the fast charging performance and power of the battery, help reduce the side reactions of positive electrode active materials, and improve the cycle performance of the battery.

[0064] In any embodiment, the first positive electrode active material has a layered structure; and / or the second positive electrode active material has an olivine structure.

[0065] In any embodiment, the first positive electrode active material includes a core and a coating layer coating the core, and the core is a compound Li a Ni b Co c M1 d M2 e O f E g and / or,

[0066] The second positive electrode active material includes a core and a coating layer covering the core, wherein the core is a compound Li x H y Mn 1-z Q z P 1- m G m O 4-n D n ;

[0067] Optionally, the coating layers in the first positive electrode active material and the second positive electrode active material independently include one or more of pyrophosphate, phosphate and carbon.

[0068] Therefore, the coating layer in the first positive electrode active material and / or the second positive electrode active material is beneficial to protecting the core, thereby reducing the occurrence of side reactions and improving the cycle performance of the battery.

[0069] In any embodiment, the coating layer accounts for 0.5% to 2.2% by mass of the second positive electrode active material, optionally 1% to 1.9%, and more optionally 1.2% to 1.5%;

[0070] Optionally, the coating layer in the second positive electrode active material is carbon.

[0071] The second aspect of the present application also provides an electrical device, comprising the battery of the first aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0072] Figure 1 is a schematic diagram of a secondary battery according to one embodiment of the present application.

[0073] Figure 2 yes Figure 1 An exploded view of a secondary battery according to an embodiment of the present application is shown.

[0074] Figure 3 is a schematic diagram of a battery module according to an embodiment of the present application.

[0075] Figure 4It is a schematic diagram of a battery pack according to one embodiment of the present application.

[0076] Figure 5 yes Figure 4 An exploded view of a battery pack according to an embodiment of the present application is shown.

[0077] Figure 6 FIG. 1 is a schematic diagram of an electric device using a secondary battery according to an embodiment of the present application as a power source.

[0078] Description of reference numerals:

[0079] 1 battery pack; 2 upper box; 3 lower box; 4 battery module; 5 secondary battery; 51 shell; 52 electrode assembly; 53 top cover assembly. DETAILED DESCRIPTION

[0080] Below, the embodiments of the battery, battery module and electrical device of the present application are specifically disclosed in detail with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0081] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values ​​or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0082] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0083] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0084] Unless otherwise specified, all steps of the present application may be performed sequentially or randomly, preferably sequentially. For example, a method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, a method may also include step (c), which means that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0085] If there is no special explanation, the "include" and "comprising" mentioned in this application represent open-ended or closed-ended expressions. For example, "include" and "comprising" may represent that other components not listed may also be included or only listed components may be included or only listed components may be included.

[0086] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0087] If there is no special explanation, in this application, the term " v The “50 particle size” refers to the particle size at which the volume accumulation is 50% from the smaller particle size side in the volume-based particle size distribution.

[0088] If there is no special explanation, in this application, the term " v The "99th particle size" refers to the particle size that reaches 99% of the volume accumulation from the small particle size side in the volume-based particle size distribution.

[0089] If not specifically stated otherwise, in the present application, the term "single crystal or single crystal-like material particle" refers to a single particle (ie, a primary particle).

[0090] If not specifically stated otherwise, in the present application, the terms "secondary particles" and "polycrystalline material particles" generally have similar meanings, which refer to particles formed by agglomeration of more than 100 primary particles having an average particle size in the range of 50-800 nm.

[0091] Unless otherwise specified, in this application, if the number and average particle size of primary particles in more than 50% (including 50%) of the agglomerated particles collected meet the definition of the above "polycrystalline material particles", then the positive electrode active material is a polycrystalline material; otherwise, it is a single crystal or quasi-single crystal material.

[0092] [Secondary battery]

[0093] A secondary battery, also known as a rechargeable battery or a storage battery, refers to a battery that can be activated by charging after discharging so that it can be used continuously.

[0094] Generally, a secondary battery includes a positive electrode plate, a negative electrode plate, a separator, and an electrolyte. During the charge and discharge process of the battery, active ions (such as lithium ions) are embedded and extracted back and forth between the positive electrode plate and the negative electrode plate. The separator is disposed between the positive electrode plate and the negative electrode plate, mainly to prevent short circuit between the positive and negative electrodes, and at the same time allows active ions to pass through. The electrolyte is between the positive electrode plate and the negative electrode plate, mainly to conduct active ions.

[0095] An embodiment of the present application provides a battery, including a positive electrode plate, the positive electrode plate including a first positive electrode active material and a second positive electrode active material; wherein,

[0096] The first positive electrode active material includes the compound Li a Ni b Co c M1 d M2 e O f E g ; wherein,

[0097] M1 includes one or two elements of Mn and Al;

[0098] M2 includes one or more elements of Zr, Zn, Cu, Cr, Mg, Fe, V, Ti, Sr, Sb, Y, W, and Nb;

[0099] E includes one or more elements of N, F, S, and Cl;

[0100] 0.75 ≤ a ≤ 1.2; 0 < b < 1; 0 < c < 1; 0 < d < 1; 0 ≤ e ≤ 0.2; 1 ≤ f ≤ 2.5, 0 ≤ g ≤ 1, and f + g ≤ 3;

[0101] The second positive electrode active material includes the compound Li x H y Mn 1-z Q z P 1-m G m O 4-n D n,in,

[0102] H includes one or more elements selected from Zn, Al, Na, K, Mg, Nb, Mo and W;

[0103] Q comprises one or more elements selected from Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ni, Co, Ga, Sn, Sb, Nb and Ge;

[0104] G includes one or more elements selected from B, Si, N, S, F, Cl and Br;

[0105] D comprises one or more elements selected from S, F, Cl and Br;

[0106] x is 0.9 to 1.1; y is 0 to 0.1; z is 0.001 to 0.9; m is 0 to 0.1; n is 0 to 0.1;

[0107] In addition, the battery meets the following requirements:

[0108]

[0109] in,

[0110] A represents the mass percentage of the second positive electrode active material in the two positive electrode active materials;

[0111] B represents the proportion of the charging capacity of the second positive electrode active material less than 3.7V in the entire charging capacity measured by the single particle microelectrode method;

[0112] C represents the proportion of the battery's charging capacity less than 3.7V in the total charging capacity;

[0113] R represents the resistance of the positive electrode at 25°C, in Ω.

[0114] The diffusion coefficient of the first positive electrode active material in the low SOC range of less than 3.7V is small, resulting in a narrower charge rate tolerance margin in the low SOC range of the battery, which affects the fast charging performance of the battery. Although the mechanism is not clear, the applicant unexpectedly discovered that: the present application combines the first positive electrode active material with the second positive electrode active material and defines Between 0.1 and 0.75, the proportion of the battery's charging capacity in the low SOC range of less than 3.7V in the total charging capacity is increased, and the charging rate tolerance boundary in the low SOC range is improved. At the same time, the proportion of the charging capacity in the high SOC range in the total charging capacity is maintained, and the deterioration of the charging rate tolerance boundary in the high SOC range is alleviated, thereby improving the battery's fast charging performance and the battery's cycle performance.

[0115] In some embodiments,

[0116] Optionally,

[0117] For example it can be 0.1, 0.2, 0.23, 0.3, 0.32, 0.38, 0.4, 0.43, 0.45, 0.49, 0.5, 0.52, 0.53, 0.6, 0.7, 0.73, 0.75, and the range composed of any of the above values.

[0118] Thus, a more suitable charging rate tolerance boundary in the low SOC range and a charging rate tolerance boundary in the high SOC range can be obtained, thereby further improving the fast charging performance and / or cycling performance of the battery.

[0119] In some embodiments, A is from 0.1 to 0.5, optionally from 0.1 to 0.3, more optionally from 0.2 to 0.3, for example it can be 0.1, 0.2, 0.3, 0.4, 0.5, and the range composed of any of the above values; and / or,

[0120] B is from 0.4 to 0.6, optionally from 0.5 to 0.6, for example it can be 0.4, 0.45, 0.48, 0.5, 0.55, 0.57, 0.6, and the range composed of any of the above values; and / or,

[0121] C is from 0.05 to 0.23, optionally from 0.09 to 0.16, for example it can be 0.09, 0.1, 0.13, 0.16, 0.18, 0.2, 0.21, 0.23, and the range composed of any of the above values; and / or,

[0122] 0 < R < 1, optionally from 0.1 to 0.6, more optionally from 0.2 to 0.4, for example 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, and the range composed of any of the above values.

[0123] In some embodiments, measure the capacity-voltage curve of the discharge process. The X-axis represents the charging capacity, the Y-axis represents the voltage. The maximum value of the Y-axis represents the full charge voltage V1, the minimum value represents the full discharge voltage V2, and V2 < 3.7V < V1. The capacity corresponding to the voltage 3.7V in the curve is Q1, the capacity Q2 corresponding to the full discharge voltage V2 is the "entire charging capacity", Q2 - Q1 represents the "charging capacity less than 3.7V", and Q1 represents the "charging capacity in the high SOC range".

[0124] In some embodiments, B represents the proportion of the charging capacity less than 3.7V of the second positive electrode active material measured by the single particle microelectrode method at 25°C in the entire charging capacity.

[0125] In some embodiments, C represents the proportion of the charge capacity of the battery less than 3.7V measured at 25°C in the total charge capacity.

[0126] In some embodiments, the charging capacity less than 3.7V and the entire charging capacity of the second positive electrode active material are determined by a single-particle microelectrode method, which is a commonly used method in the field. For example, the single-particle microelectrode method mainly includes a microelectrode, a microscope, a micromanipulator and an electrochemical workstation. The microelectrode is moved by a micromanipulator in combination with a microscope to make the microelectrode contact with a single particle of the second positive electrode active material. Then, an electrochemical test is performed at a certain temperature using a single particle as a working electrode, a lithium strip as a counter electrode and a reference electrode, and a certain electrolyte to obtain a capacity-voltage curve of the discharge process.

[0127] In some embodiments, the less than 3.7V charging capacity and the entire charging capacity of the battery can be measured by conventional methods in the art, such as charging and discharging three times, and obtaining the less than 3.7V charging capacity and the entire charging capacity of the battery from the capacity-voltage curve of the third discharge process.

[0128] In some embodiments, R can be measured using conventional methods and equipment in the art, such as using a BER1300 film resistor meter for testing at a test temperature of 25°C.

[0129] A, B, and C within the above range can further improve the charge rate tolerance boundary in the low SOC interval, and make the charge rate tolerance boundary in the high SOC interval more suitable, thereby further improving the fast charging performance and / or cycle performance of the battery;

[0130] R within the above range can obtain a lower overpotential, which is beneficial to improving the rate performance of the battery and making the charging process go smoothly.

[0131] In some embodiments, in the second positive electrode active material, Q includes one or more elements of Fe, Ti, V, Ni, Co and Mg; and / or,

[0132] G includes one or more elements of B, Si, N and S; and / or,

[0133] x is 0.977 to 1, for example, 0.977, 0.98, 0.985, 0.99, 0.992, 0.994, 1, and any range thereof; and / or,

[0134] y is 0 to 0.001, for example, 0, 0.0005, 0.001, and any range thereof; and / or,

[0135] z is 0.1 to 0.9 or 0.001 to 0.6, and can be 0.3 to 0.7, for example, 0.001, 0.005, 0.01, 0.05, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9 and any range thereof; and / or,

[0136] m is 0 to 0.001 or 0.001 to 0.1, for example, 0, 0.0005, 0.001, 0.005, 0.01, 0.02, 0.04, 0.05, 0.07, 0.08, 0.1, and any range thereof; and / or,

[0137] n is 0 to 0.001 or 0.001 to 0.1, for example, may be 0, 0.0005, 0.001, 0.005, 0.01, 0.02, 0.04, 0.05, 0.07, 0.08, 0.1, or a range consisting of any of the above values.

[0138] Thus, by using a second positive electrode active material including the above-mentioned Q and G elements, the proportion of the battery's charging capacity in the low SOC range of less than 3.7V in the total charging capacity can be further increased, and the charging rate tolerance boundary in the low SOC range can be further improved. At the same time, the proportion of the charging capacity in the high SOC range in the total charging capacity can be maintained, and the deterioration of the charging rate tolerance boundary in the high SOC range can be alleviated, thereby further improving the battery's fast charging performance and / or cycle performance.

[0139] In some embodiments, in the first positive electrode active material, a is 0.9 to 1.1, for example, 0.75, 0.8, 0.85, 0.9, 0.95, 1, 1.1, 1.2, and any range thereof; and / or,

[0140] d is 0.003 to 0.4, for example, 0.003, 0.005, 0.008, 0.01, 0.03, 0.04, 0.05, 0.07, 0.1, 0.13, 0.15, 0.2, 0.24, 0.26, 0.3, 0.33, 0.35, 0.38, 0.4, and any range thereof; and / or,

[0141] b is 30% to 99.5%, optionally 50% to 99%, more optionally 55% to 88%, for example, it can be 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 0.95, 0.995 and any range thereof; and / or,

[0142] c is 0.2% to 52%, and can be optionally 0.5% to 49.5%, and can be more optionally 5% to 35%. For example, it can be 0.002, 0.005, 0.008, 0.01, 0.03, 0.06, 0.08, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.48, 0.5, 0.52, and a range consisting of any of the above values.

[0143] The Ni content within the above range can improve the fast charging performance and / or cycle performance of the battery.

[0144] The Co content within the above range can improve the fast charging performance and / or cycle performance of the battery.

[0145] In some embodiments, the first cathode material is a single crystal or quasi-single crystal material and satisfies:

[0146] D of single crystal particles or quasi-single crystal particles v 50 The particle size is 1.5 to 4.5 μm, and can be 2 to 4.1 μm, for example, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.2 μm, 3.5 μm, 4 μm, 4.2 μm, 4.5 μm, and any range thereof; and / or,

[0147] D of single crystal particles or quasi-single crystal particles v 99 The particle size is ≤18μm, which can be 6.4 to 17.5μm, and more preferably 6.5 to 13.5μm, for example, it can be 1μm, 2μm, 3μm, 4μm, 5μm, 5.5μm, 6μm, 6.4μm, 7μm, 7.5μm, 8μm, 8.5μm, 9μm, 9.5μm, 10μm, 10.4μm, 11μm, 11.6μm, 12μm, 12.5μm, 13μm, 13.6μm, 14μm, 14.5μm, 15μm, 15.5μm, 16μm, 16.4μm, 17μm, 17.5μm, 18μm and the range composed of any of the above values; and / or,

[0148] The BET specific surface area of ​​the first positive electrode active material is 0.42 to 1.2 m 2 / g, optional 0.5 to 1m 2 / g, for example, 0.42m 2 / g, 0.47m 2 / g, 0.5m 2 / g, 0.55m 2 / g, 0.58m 2 / g, 0.6m 2 / g, 0.65m 2 / g, 0.68m 2 / g, 0.7m2 / g, 0.75m 2 / g, 0.8m 2 / g, 0.85m 2 / g, 0.9m 2 / g, 0.95m 2 / g, 1.0m 2 / g, 1.1m 2 / g, 1.2m 2 / g and any range consisting of the above values.

[0149] When the first positive electrode active material is a single crystal or a quasi-single crystal material, D within the above range v 50 particle size, D v 99 particle size and BET specific surface area are beneficial to increase the active sites of positive electrode active materials, improve the fast charging performance and power of the battery, help reduce the side reactions of positive electrode active materials, and improve the cycle performance of the battery.

[0150] In some embodiments, the first positive electrode active material is a polycrystalline material and satisfies:

[0151] The Dv50 particle size of the secondary particles is 6 to 14 μm, and can be 7 to 13 μm, for example, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, and any range thereof; and / or,

[0152] The Dv99 particle size of the secondary particles is less than 30 μm, and may be 14.2 to 28.8 μm, and more preferably 15.4 to 26.7 μm, for example, 6 μm, 10 μm, 11 μm, 13 μm, 15 μm, 17 μm, 18 μm, 20 μm, 21 μm, 22 μm, 24 μm, 26 μm, 27 μm, 28 μm, 29 μm, and any range thereof; and / or,

[0153] The particle size of the primary particles is 50 to 800 nm, and can be 50 to 600 nm, for example, 50 nm, 55 nm, 60 nm, 65 nm, 70 nm, 80 nm, 90 nm, 100 nm, 120 nm, 150 nm, 200 nm, 240 nm, 260 nm, 300 nm, 350 nm, 400 nm, 450 nm, 500 nm, 550 nm, 600 nm, 650 nm, 700 nm, 750 nm, 800 nm, and any range consisting of the above values; and / or,

[0154] The BET specific surface area of ​​the first positive electrode active material is 0.8 to 1.2 m 2 / g, optional 0.8 to 1.1m 2 / g, for example, 0.85m2 / g, 0.9m 2 / g, 0.95m 2 / g, 0.98m 2 / g, 1.0m 2 / g, 1.05m 2 / g, 1.1m 2 / g, 1.2m 2 / g and any range consisting of the above values.

[0155] When the first positive electrode active material is a polycrystalline material, the secondary particles D within the above range v 50 particle size, secondary particle D v 99 particle size, primary particle size, and BET specific surface area are beneficial to increasing the active sites of the positive electrode active material, improving the fast charging performance and power of the battery, helping to reduce the side reactions of the positive electrode active material, and improving the cycle performance of the battery.

[0156] In some embodiments, the second positive electrode active material is a single crystal or a quasi-single crystal material and satisfies:

[0157] D of single crystal particles or single crystal-like particles v 50 The particle size is 0.2 to 1.6 μm, and can be 0.25 to 1.49 μm, for example, 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1.0 μm, 1.1 μm, 1.2 μm, 1.3 μm, 1.4 μm, 1.5 μm, 1.6 μm, and any range thereof; and / or,

[0158] D of single crystal particles or single crystal-like particles v 99 The particle size is 5.2 to 33.8 μm, and can be 6.1 to 25.7 μm, for example, 5.2 μm, 5.5 μm, 6 μm, 6.5 μm, 7 μm, 7.5 μm, 8 μm, 8.5 μm, 9 μm, 9.5 μm, 10 μm, 10.5 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 18 μm, 20 μm, 22 μm, 24 μm, 26 μm, 28 μm, 30 μm, 31 μm, 33 μm, 33.8 μm, and any range thereof; and / or,

[0159] The BET specific surface area of ​​the second positive electrode active material is 11.3 to 14.1 m 2 / g, optional 12 to 13.7m 2 / g, for example, 11.3m 2 / g, 11.5m 2 / g, 12m 2 / g, 12.5m2 / g, 12.8m 2 / g, 13m 2 / g, 13.6m 2 / g, 14m 2 / g, 14.1m 2 / g and any range consisting of the above values.

[0160] When the second positive electrode active material is a single crystal or a quasi-single crystal material, the above range of D v 50 particle size, D v 99 particle size and BET specific surface area are beneficial to increase the active sites of positive electrode active materials, improve the fast charging performance and power of the battery, help reduce the side reactions of positive electrode active materials, and improve the cycle performance of the battery.

[0161] In some embodiments, the crystal form can be determined by conventional methods in the art, such as testing the sample using a scanning electron microscope, adjusting the magnification so that there are more than 10 agglomerated particles in the field of view, measuring the number of primary particles that make up each agglomerated particle, and using a ruler to measure the length direction of the primary particle as the particle size, sorting the particle size of the primary particles in each agglomerated particle from large to small, removing 1 / 10 of the maximum particle size data and 1 / 10 of the minimum particle size data, and taking the average of the remaining particle size data as the average particle size of the primary particles in the agglomerated particle. If the number and average particle size of the primary particles in more than 50% (including 50%) of the agglomerated particles meet the definition of the aforementioned "polycrystalline material particles", the sample is determined to be a polycrystalline material, otherwise, it is determined to be a single crystal or quasi-single crystal material. The average particle size of the primary particles is taken as the particle size of the primary particles of the polycrystalline material.

[0162] In some embodiments, D v 50 particle size and D v The particle size can be determined by conventional methods in the art, for example, according to the method in the national standard GB / T 19077-2016 "Particle size distribution laser diffraction method".

[0163] In some embodiments, the BET specific surface area is the BET specific surface area at 25°C.

[0164] In some embodiments, the BET specific surface area can be measured using conventional methods in the art, for example, according to the method in the national standard GB / T 19587-2004 "Determination of the specific surface area of ​​solid substances by gas adsorption BET method".

[0165] In some embodiments, the first cathode active material has a layered structure; and / or the second cathode active material has an olivine structure.

[0166] In some embodiments, the first positive electrode active material includes a core and a coating layer coating the core, wherein the core is a compound Li a Ni b Co c M1 d M2 e O f E g and / or,

[0167] The second positive electrode active material includes a core and a coating layer covering the core, wherein the core is a compound Li x H y Mn 1-z Q z P 1- m G m O 4-n D n ;

[0168] Optionally, the coating layers in the first positive electrode active material and the second positive electrode active material independently include one or more of pyrophosphate, phosphate and carbon.

[0169] Therefore, the coating layer in the first positive electrode active material and / or the second positive electrode active material is beneficial to protecting the core, thereby reducing the occurrence of side reactions and improving the cycle performance of the battery.

[0170] In some embodiments, the coating layer accounts for 0.5% to 2.2% by mass of the second positive electrode active material, optionally 1% to 1.9%, and more optionally 1.2% to 1.5%;

[0171] Optionally, the coating layer in the second positive electrode active material is carbon.

[0172] In some embodiments, the battery includes a negative electrode plate, the negative electrode plate includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector, and the negative electrode film layer contains a negative electrode active material; wherein,

[0173] The coating surface density of the negative electrode active material is 9 to 11 mg / cm, and can be 9.5 to 10.5 mg / cm 2 , more preferably 10.0 to 10.4 mg / cm; and / or,

[0174] The density of the negative electrode film is 1.55 to 1.75 g / cm 3 , optional 1.6 to 1.7 g / cm 3 , and can be selected from 1.64 to 1.69 g / cm 3 .

[0175] The coating surface density of the negative electrode active material within the above range is conducive to improving the fast charge rate performance of the battery, improving the charging CB of the battery, and alleviating the lithium plating problem of the negative electrode sheet. The density of the negative electrode film layer within the above range is conducive to improving the lithium insertion capacity of the negative electrode sheet and the contact between the negative electrode active material and the conductive agent, thereby improving the fast charge rate performance and / or cycle performance of the battery.

[0176] In some embodiments, “coating area density of negative electrode active material” refers to the weight of negative electrode active material contained in a unit area of ​​a negative electrode sheet.

[0177] [Positive electrode]

[0178] The positive electrode sheet generally includes a positive electrode current collector and a positive electrode film layer disposed on at least one surface of the positive electrode current collector, and the positive electrode film layer includes the first positive electrode active material and the second positive electrode active material mentioned above.

[0179] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.

[0180] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0181] In some embodiments, the positive electrode film layer may also optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.

[0182] In some embodiments, the positive electrode film layer may further include a conductive agent, for example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.

[0183] In some embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.

[0184] [Negative electrode]

[0185] The negative electrode plate includes a negative electrode current collector and a negative electrode film layer arranged on at least one surface of the negative electrode current collector, and the negative electrode film layer includes a negative electrode active material.

[0186] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.

[0187] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, a copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0188] In some embodiments, the negative electrode active material may adopt the negative electrode active material for the battery known in the art. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.

[0189] In some embodiments, the negative electrode film layer may further include a binder. As an example, the binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).

[0190] In some embodiments, the negative electrode film layer may further include a conductive agent. As an example, the conductive agent may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0191] In some embodiments, the negative electrode film layer may optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).

[0192] In some embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.

[0193] [Electrolytes]

[0194] The electrolyte plays the role of conducting ions between the positive electrode and the negative electrode. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid, gel or all-solid.

[0195] In some embodiments, the electrolyte is liquid and includes an electrolyte salt and a solvent.

[0196] In some embodiments, the electrolyte salt can be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.

[0197] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.

[0198] In some embodiments, the electrolyte may further include additives. As examples, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.

[0199] [Isolation film]

[0200] In some embodiments, the secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical stability and mechanical stability can be selected.

[0201] In some embodiments, the material of the isolation membrane can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.

[0202] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator may be formed into an electrode assembly by a winding process or a lamination process.

[0203] In some embodiments, the secondary battery may include an outer package, which may be used to encapsulate the electrode assembly and the electrolyte.

[0204] In some embodiments, the outer packaging of the secondary battery may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.

[0205] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square or any other shape. Figure 1 The secondary battery 5 is a square structure as an example.

[0206] In some embodiments, reference Figure 2 , the outer package may include a shell 51 and a cover plate 53. Among them, the shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. ​​The number of electrode assemblies 52 contained in the secondary battery 5 can be one or more, and those skilled in the art can select according to specific actual needs.

[0207] In some embodiments, secondary batteries may be assembled into a battery module. The number of secondary batteries contained in the battery module may be one or more, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery module.

[0208] Figure 3 4 is an example of a battery module. Figure 3In the battery module 4, the plurality of secondary batteries 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of secondary batteries 5 may be fixed by fasteners.

[0209] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of secondary batteries 5 are received in the receiving space.

[0210] In some embodiments, the battery modules described above may also be assembled into a battery pack. The battery pack may contain one or more battery modules, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery pack.

[0211] Figure 4 and Figure 5 1 is a battery pack 1 as an example. Figure 4 and Figure 5 The battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the battery box in any manner.

[0212] In the present application, the battery may include but is not limited to a secondary battery, a battery module, and a battery pack.

[0213] In addition, the present application also provides an electrical device, which includes at least one of the secondary battery, battery module, or battery pack provided in the present application. The secondary battery, battery module, or battery pack can be used as a power source for the electrical device, or as an energy storage unit for the electrical device. The electrical device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.

[0214] As an electrical device, a secondary battery, a battery module or a battery pack can be selected according to its usage requirements.

[0215] Figure 6 The power consumption device is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the high power and high energy density requirements of the power consumption device for the secondary battery, a battery pack or a battery module can be used.

[0216] [Example]

[0217] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.

[0218] Example 1

[0219] (1) The first positive electrode active material was purchased from Guangdong Brunp Recycling Technology Co., Ltd.

[0220] (2) Second positive electrode active material: purchased from Shenzhen Defang Nanotechnology Co., Ltd.

[0221] (3) Preparation of positive electrode sheet: The first positive electrode active material, the second positive electrode active material, polyvinylidene fluoride (PVDF) and conductive carbon were added to N-methylpyrrolidone (NMP) in a mass ratio of 63:27:5:5, and stirred in a drying room to form a uniform slurry with a viscosity controlled to be 3000 to 10000 mPa·s. The slurry was coated on the positive electrode current collector aluminum foil and dried to form a positive electrode sheet.

[0222] (4) Preparation of negative electrode sheet: Graphite, sodium carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), and conductive carbon were added to deionized water in a mass ratio of 90:2:3:5, stirred to form a uniform slurry, and the viscosity was controlled to be 3000-10000 mPa·S. The above negative electrode slurry was coated on the negative electrode current collector copper foil, and dried to form a negative electrode sheet.

[0223] (5) Isolation membrane: Polyethylene (PE) porous polymer film is used.

[0224] (6) Preparation of electrolyte: Ethylene carbonate (EC), diethyl carbonate (DEC) and dimethyl carbonate (DMC) were mixed at a volume ratio of 1:1:1, and then LiPF6 and fluoroethylene carbonate (FEC) were uniformly dissolved in the above solution to obtain an electrolyte. In the electrolyte, the concentration of LiPF6 was 1 mol / L, and the content of fluoroethylene carbonate (FEC) was 5 wt.%.

[0225] (7) Preparation of soft-pack laminated battery: The above-mentioned positive electrode plate, negative electrode plate and separator are made into corresponding battery cells according to the Z-shaped laminated structure, and the battery cells are vacuum dried at 90°C for 12 hours, and then the positive and negative electrode tabs are ultrasonically welded. The positive electrode uses aluminum tabs and the negative electrode uses nickel tabs. The positive and negative electrode tabs are located on the same side of the battery cell. The battery cell after the tabs are welded is placed in an aluminum-plastic film of appropriate size for top-side packaging. The normal packaging temperature is 145°C. Liquid injection, standing, formation, aging, exhaust, secondary sealing, and capacity testing are performed to obtain the prepared soft-pack laminated battery.

[0226] The secondary battery preparation methods of Examples 2-41 and Comparative Examples 1-2 are similar to those of Example 1, and the different product parameters are detailed in Table 1. Among them:

[0227] A represents the mass percentage of the second positive electrode active material in the two positive electrode active materials;

[0228] B represents the proportion of the charging capacity of the second positive electrode active material less than 3.7V in the entire charging capacity measured by the single particle microelectrode method;

[0229] C represents the proportion of the battery's charging capacity less than 3.7V in the total charging capacity;

[0230] R represents the resistance of the positive electrode at 25°C (Ω).

[0231] In Table 1, the first positive electrode active material is a layered structure, all of which are purchased from Guangdong Brunp Recycling Technology Co., Ltd.; the second positive electrode active materials of Examples 1-38 are olivine-type, all of which are purchased from Shenzhen Defang Nanotechnology Co., Ltd.

[0232] Example 39 Preparation method of the second positive electrode active material

[0233] Preparation of doped manganese oxalate: 1.3 mol of MnSO4﹒H2O and 0.7 mol of FeSO4﹒H2O were fully mixed in a mixer for 6 hours. The mixture was transferred to a reactor, and 10 L of deionized water and 2 mol of dihydrated oxalic acid (calculated as oxalic acid) were added. The reactor was heated to 80°C and stirred at 600 rpm for 6 hours. The reaction was terminated (no bubbles were generated) to obtain a Fe-doped manganese oxalate suspension. The suspension was then filtered, and the filter cake was dried at 120°C and then ground to obtain a median particle size Dv 50 Fe-doped manganese oxalate particles with a size of about 100 nm.

[0234] Preparation of doped lithium manganese phosphate: 1 mol of the above manganese oxalate particles, 0.497 mol of lithium carbonate, 0.001 mol of Mo(SO4)3, 0.999 mol of phosphoric acid in an 85% phosphoric acid aqueous solution, 0.001 mol of H4SiO4, 0.0005 mol of NH4HF2 and 0.005 mol of sucrose are added to 20 L of deionized water. The mixture is transferred to a sand mill and fully ground and stirred for 10 hours to obtain a slurry. The slurry is transferred to a spray drying device for spray drying and granulation, the drying temperature is set to 250°C, and dried for 4 hours to obtain particles. In a nitrogen (90 volume %) + hydrogen (10 volume %) protective atmosphere, the above powder is sintered at 700°C for 10 hours. The positive electrode active material can be detected for element content by inductively coupled plasma emission spectroscopy (ICP).

[0235] Example 40 Preparation method of the second positive electrode active material

[0236] The preparation method of the second positive electrode active material is the same as that of Example 1-36, except that the amount of high-purity Li2CO3 is changed to 0.4885 mol, Mo(SO4)3 is replaced by MgSO4, the amount of FeSO4﹒H2O is changed to 0.68 mol, 0.02 mol of Ti(SO4)2 is added when preparing doped manganese oxalate, and H4SiO4 is replaced by HNO3. The positive electrode active material can be detected by inductively coupled plasma emission spectroscopy (ICP) for element content.

[0237] Example 41 Preparation method of the second positive electrode active material

[0238] The preparation method of the second positive electrode active material is the same as that of Example 1-36, except that the amount of high-purity Li2CO3 is changed to 0.496 mol, Mo(SO4)3 is replaced by W(SO4)3, and H4SiO4 is replaced by H2SO4. The positive electrode active material can be detected by inductively coupled plasma emission spectroscopy (ICP) for element content.

[0239]

[0240]

[0241]

[0242]

[0243]

[0244]

[0245]

[0246]

[0247] Battery Test

[0248] (1) Resistance measurement of positive electrode sheet:

[0249] The test was performed using a BER1300 film resistor meter. The test steps are as follows:

[0250] a) The positive electrode sheet is made into a disc with a diameter of 22 mm;

[0251] b) Place the prepared wafer on the test platform of the BER1300 instrument for testing. The test pressure is 0.4 tons, the test temperature is 25°C, and the test time is 10s. The resistance value obtained is the resistance of the positive electrode.

[0252] (2) Determination of the proportion of the second positive electrode active material's charge capacity less than 3.7V in the total charge capacity (single particle microelectrode method):

[0253] The particles of the second positive electrode active material (Dv50 particle size of 0.25-1.49 μm) were dispersed on a coverslip washed successively with a washing solution (a 98 wt % H 2 SO 4 aqueous solution and a 30 wt % hydrogen peroxide solution mixed in a volume ratio of 3:1) and deionized water.

[0254] The microelectrode is a platinum wire encapsulated by a glass capillary. The diameter of the platinum wire is 10 μm. The radius ratio of the glass capillary to the platinum wire is less than 5. The end face of the platinum wire is polished into a needle tip shape. The platinum wire and the copper wire are connected by conductive silver glue. Before the test, the microelectrode needs to be placed in a 0.5 mol / L H2SO4 aqueous solution for cyclic voltammetry scanning at a scanning speed of 50 mV / s and a scanning potential range of -0.22V to 1.22V (vs. SCE) to remove impurities remaining on the microelectrode.

[0255] The single-particle microelectrode test device mainly includes a microelectrode, a microscope, a micromanipulator and an electrochemical workstation. The microelectrode is moved by the micromanipulator in combination with the microscope to make the microelectrode contact with a single particle of the second positive electrode active material. Then, the single particle is used as the working electrode, the lithium strip is used as the counter electrode and the reference electrode, and ethylene carbonate (EC) and propylene carbonate (PC) (volume ratio 1:1) containing 1 mol / L LiPF6 are used as the electrolyte for electrochemical testing; the electrochemical test temperature is 25°C, and the constant current is charged to 4.4V at 0.33C and then switched to constant voltage charging. When the charging current decreases to 0.05C, the constant voltage charging ends, and then the battery is discharged at 0.33C to a full discharge voltage of 2.5V. The capacity-voltage curve of the discharge process is taken, the X-axis represents the charging capacity, the Y-axis represents the voltage, the charging capacity corresponding to the voltage of 3.7V is Q3, and the full discharge voltage of 2.5V corresponds to the entire charging capacity Q4. The proportion B of the charging capacity with a voltage less than 3.7V in the entire charging capacity is calculated according to the following formula.

[0256] B(%)=100×(Q4-Q3) / Q4

[0257] (3) Determination of the proportion of battery charging capacity less than 3.7V in the total charging capacity:

[0258] The soft-pack laminated battery was tested, and the operation was as follows: the test environment temperature was 25°C, and it was charged to 4.4V at a constant current of 0.33C and then switched to constant voltage charging. When the charging current decreased to 0.05C, the constant voltage charging ended, and then it was discharged at 0.33C to a full discharge voltage of 2.5V. This process was repeated 3 times, and the capacity-voltage curve of the third discharge process was taken. The X-axis represents the charging capacity, and the Y-axis represents the voltage. The charging capacity corresponding to the voltage of 3.7V is Q1, and the full discharge voltage of 2.5V corresponds to the entire charging capacity Q2. The proportion C of the battery's charging capacity less than 3.7V in the entire charging capacity is calculated according to the following formula.

[0259] C(%)=100×(Q2-Q1) / Q2

[0260] (4) Testing of crystal type and primary particle size of polycrystalline materials:

[0261] If not specifically stated otherwise, in the present application, the term "single crystal / quasi-single crystal particle" means a single particle (ie, a primary particle).

[0262] If not specifically stated otherwise, in the present application, the terms "secondary particles" and "polycrystalline material particles" generally have similar meanings, which refer to particles formed by agglomeration of more than 100 primary particles having an average particle size in the range of 50-800 nm.

[0263] The positive electrode active material is tested by scanning electron microscope, and the sample and magnification are adjusted so that there are more than 10 agglomerated particles in the field of view, and the number of primary particles constituting each agglomerated particle is measured, and the size of the primary particle in the length direction is measured with a ruler and recorded as the particle size, and the particle size of the primary particles in each agglomerated particle is sorted from large to small, and 1 / 10 of the maximum particle size data and 1 / 10 of the minimum particle size data are removed, and the average of the remaining particle size data is taken as the average particle size of the primary particles in the agglomerated particle. If the number and average particle size of the primary particles in more than 50% (including 50%) of the agglomerated particles meet the above definition of "polycrystalline material particles", the positive electrode active material is determined to be a polycrystalline material, otherwise, it is determined to be a single crystal or quasi-single crystal material.

[0264] The average particle size of the primary particles of the polycrystalline material was recorded as the particle size of the primary particles.

[0265] (5) Particle size distribution test:

[0266] According to the method in the national standard GB / T 19077-2016 "Particle size distribution laser diffraction method", the D v 50 particle size and Dv99 particle size, wherein deionized water was used as solvent and ultrasonic treatment was performed for 5 minutes before testing.

[0267] (6) BET specific surface area test:

[0268] The test environment temperature is 25°C, and the BET specific surface area of ​​the powder is determined according to the method in the national standard GB / T 19587-2004 "Determination of the specific surface area of ​​solid substances by gas adsorption BET method". Before the test, the powder is placed in a vacuum oven at 200°C and dried for ≥2h, and the required amount of powder is weighed>20g.

[0269] (7) 10% to 80% SOC charging time test:

[0270] In a constant temperature environment of 25°C, charge-discharge tests are conducted on the soft-pack laminated battery at different rates (C1 < C2 < C3 < C4 < …… < Cn). During the test, the charging rate increases from small to large. During the charging process, the full-cell voltage and the negative electrode voltage of the soft-pack laminated battery need to be monitored simultaneously. The specific process is as follows: The soft-pack laminated battery is charged at C1 until the full-charge voltage reaches 4.4V or the negative electrode voltage is 0V, and the SOC value of the battery at the end of charging is obtained. Then, it is discharged at 0.33C until the full-discharge voltage reaches 2.5V; repeat the above process according to the charging rate increasing from small to large, and the SOC values at the end of charging at different rates can be obtained. Fit the SOC values at the end of charging with the corresponding rate values to obtain the relationship between the SOC and the rate value at the end of charging. Substitute 20% SOC, 30% SOC, 40% SOC, 50% SOC, 60% SOC, 70% SOC, 80% SOC into the relationship formula to obtain the corresponding rates C20%, C30%, C40%, C50%, C60%, C70%, C80%. Calculate the charging time (min) for 10% - 80% SOC according to the following formula;

[0271] Charging time for 10% - 80% SOC = (60 / C20% + 60 / C30% + …… + 60 / C80%) × 10%.

[0272] (8) Cycle life test:

[0273] Charge the battery at 0.5C from 2.5V to 4.25 - 4.3V in a constant temperature environment of 25°C, then perform constant voltage charging at 4.25 - 4.3V until the current ≤ 0.05mA, let it stand for 5 minutes, and then discharge it at 0.5C to 2.5V. Record the discharge capacity of the first cycle of the battery as D1; repeat the above operation, and record the discharge capacity of each cycle as D n (n = 2, 3……); Calculate the attenuation degree (State of health SOH) of the battery cell according to the following formula, and record the number of cycles n when the attenuation degree reaches 80% SOH.

[0274] Attenuation degree of the battery cell = 100% × Dn / D3

[0275] (9) Test of the density of the negative electrode film layer:

[0276] At room temperature, take an area of 10mm 2, and a disc-shaped negative electrode current collector with a thickness of d1 (mm), weighing its weight m1 (g); taking a negative electrode current collector of the same material and thickness with a length of 10m and a width of 200mm, coating the aforementioned negative electrode slurry on both sides of the negative electrode current collector, drying, and cold pressing at 30-40T to obtain a negative electrode pole piece, which includes a negative electrode current collector and a negative electrode film layer coated on the negative electrode current collector; starting from one end of the pole piece, take 10mm at 1m, 3m, 5m, 7m, and 9m in length respectively 2 Weigh the weight of each disc m2-m6 (g) and calculate the average weight of the disc m s (g) Measure the thickness d2-d6 (mm) of each disc and calculate the average thickness d s (mm); calculate the density of the negative electrode film layer (g / cm) according to the following formula 3 ).

[0277]

[0278] (10) Testing of charging CB data:

[0279] The positive electrode sheet and the negative electrode sheet are respectively assembled into button batteries (the negative electrode adopts a metal lithium sheet); the test conditions of the positive electrode sheet button battery are: at 25°C, 0.1C charge and discharge, 2.5-4.45V, the capacity of the positive electrode sheet button battery is obtained, divided by the mass of the positive electrode active material, and the gram capacity Q1 (mAh / g) of the positive electrode active material is obtained; the test conditions of the negative electrode sheet button battery are: at 25°C, 0.1C charge and discharge, 0.005-2.0V, the capacity of the negative electrode sheet button battery is obtained, divided by the mass of the negative electrode active material, and the gram capacity Q2 (mAh / g) of the negative electrode active material is obtained.

[0280] At room temperature, take an area of ​​10mm 2 The disc-shaped positive electrode current collector is weighed m1 (g); take an area of ​​10mm 2 A disc-shaped negative electrode current collector is weighed m12 (g); a positive electrode current collector of the same material and thickness is taken with a length of 10m and a width of 200mm, and the aforementioned positive electrode slurry is coated on the front and back sides of the positive electrode current collector. After drying and cold pressing, a positive electrode plate is obtained, which includes a positive electrode current collector and a positive electrode film layer coated on the positive electrode current collector, and the positive electrode active material content in the positive electrode film layer is W1; a negative electrode current collector of the same material and thickness is taken with a length of 10m and a width of 200mm, and the aforementioned negative electrode slurry is coated on the front and back sides of the negative electrode current collector. After drying and cold pressing, a negative electrode plate is obtained, which includes a negative electrode current collector and a negative electrode film layer coated on the negative electrode current collector, and the negative electrode active material content in the negative electrode film layer is W2; starting from one end of the positive electrode plate / negative electrode plate, 10mm is taken at a length of 1m, 3m, 5m, 7m, and 9m respectively 2The weight of each positive electrode disc is recorded as m2-m6 (g) and the average weight of the positive electrode disc is calculated as m s1 (g), the weight of each negative electrode disc is recorded as m7-m11 (g) and the average weight of the negative electrode disc is calculated as m s2 (g).

[0281] Calculate the charging CB value according to the following formula.

[0282] Charging CB value = (m s2 / 10-m12 / 10)×Q2×W2 / [(m s1 / 10-m1 / 10)×Q1×W1]

[0283] (11) Test of lithium deposition:

[0284] The cycled soft-pack laminated battery of item (8) is charged at a constant current of 0.33C to a full charge voltage of 4.4V, and then switched to constant voltage charging. When the charging current is reduced to 0.05C, the charging is terminated. The battery is disassembled at a relative humidity of 2% to observe whether there is silver-white metal precipitation on the surface of the negative electrode. If so, it is lithium deposition, otherwise there is no lithium deposition.

[0285] Table 2: Performance test results of Examples 1-41 and Comparative Examples 1-2

[0286]

[0287]

[0288] According to the above results, we can know that:

[0289] Compared with Comparative Examples 1-2, the battery made of the positive electrode active material in the embodiment of the present application has better fast charging performance and longer cycle life;

[0290] Compared with Examples 20-23 and 26, the fast charging performance of the batteries made of the positive electrode materials of Examples 1, 4-11, 13-18, and 31-38 of the present application is further improved, and the cycle life is further extended;

[0291] Compared with Examples 2-3, the fast charging performance of the batteries made of the positive electrode materials of Examples 1, 4-11, 13-18, and 31-38 of the present application is further improved;

[0292] Compared with Examples 12, 19, 24-25, and 27-28, the cycle life of batteries made from the positive electrode materials of Examples 1, 4-11, 13-18, and 31-38 of the present application is further extended.

[0293] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A battery, comprising a positive electrode plate, wherein the positive electrode plate comprises a first positive electrode active material and a second positive electrode active material; wherein, The first positive electrode active material includes a compound Li a Ni b Co c M1 d M2 e O f E g ;in, The M1 comprises one or two elements of Mn and Al; The M2 comprises one or more elements of Zr, Zn, Cu, Cr, Mg, Fe, V, Ti, Sr, Sb, Y, W and Nb; The E comprises one or more elements of N, F, S and Cl; 0.75 ≤ a ≤ 1.2; 0 < b < 1; 0 < c < 1; 0 < d < 1; 0 ≤ e ≤ 0.2; 1 ≤ f ≤ 2.5, 0 ≤ g ≤ 1, and f + g ≤ 3; The second positive electrode active material includes a compound Li x H y Mn 1-z Q z P 1-m G m O 4-n D n ,in, The H comprises one or more elements selected from Zn, Al, Na, K, Mg, Nb, Mo and W; The Q comprises one or more elements selected from Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ni, Co, Ga, Sn, Sb, Nb and Ge; The G comprises one or more elements selected from B, Si, N, S, F, Cl and Br; The D comprises one or more elements selected from S, F, Cl and Br; The x is from 0.9 to 1.1; the y is from 0 to 0.1; the z is from 0.001 to 0.9; the m is from 0 to 0.1; the n is from 0 to 0.1; And, the battery satisfies: Wherein, A represents the mass percentage of the second positive electrode active material in the two positive electrode active materials; B represents the proportion of the charging capacity less than 3.7V of the second positive electrode active material measured by the single-particle microelectrode method in the total charging capacity; C represents the proportion of the charging capacity less than 3.7V of the battery in the total charging capacity; R represents the resistance of the positive electrode plate at 25°C, with the unit of Ω.

2. The battery according to claim 1, wherein, 3. The battery according to claim 1, wherein 4. The battery according to claim 1, wherein, The A is from 0.1 to 0.5; and / or, The B is from 0.4 to 0.6; and / or, The C is from 0.05 to 0.23; and / or, 0<R<1。 5. The battery according to claim 1, characterized in that One or more of the following: The A is from 0.1 to 0.3; The A is from 0.2 to 0.3; The B is from 0.5 to 0.6; The C is from 0.09 to 0.16; The R is from 0.1 to 0.6; The R is from 0.2 to 0.

4.

6. The battery according to claim 1, wherein In the second positive electrode active material, the Q comprises one or more elements of Fe, Ti, V, Ni, Co and Mg; and / or, The G comprises one or more elements of B, Si, N and S; and / or, The x is from 0.977 to 1; and / or, The y is from 0 to 0.001; and / or, The z is from 0.1 to 0.9, from 0.001 to 0.6 or from 0.3 to 0.7; and / or, The m is from 0 to 0.001 or from 0.001 to 0.1; and / or, The n is from 0 to 0.001 or from 0.001 to 0.

1.

7. The battery according to claim 1, wherein In the first positive electrode active material, the a is from 0.9 to 1.1; and / or, The d is from 0.003 to 0.4; and / or, The b is from 30% to 99.5%; and / or, The c is from 0.2% to 52%.

8. The battery according to claim 1, wherein The first positive electrode active material includes one or more of the following: The b is 50% to 99%; The b is 55% to 88%; The c is 0.5% to 49.5%; The c is 5% to 35%.

9. The battery according to claim 1, wherein The first positive electrode material is a single crystal or a quasi-single crystal material and satisfies: D of single crystal particles or single crystal-like particles v 50 particle size of 1.5 to 4.5 μm; and / or, D of single crystal particles or single crystal-like particles v 99 Particle size ≤ 18 μm; and / or, The BET specific surface area of ​​the first positive electrode active material is 0.42 to 1.2 m 2 / g.

10. The battery according to claim 1, wherein The first cathode material is a single crystal or quasi-single crystal material, and includes one or more of the following: D of single crystal particles or single crystal-like particles v 50 Particle size is 2 to 4.1 μm; D of single crystal particles or single crystal-like particles v 99 Particle size is 6.4 to 17.5 μm; D of single crystal particles or single crystal-like particles v 99 Particle size is 6.5 to 13.5 μm; The BET specific surface area of ​​the first positive electrode active material is 0.5 to 1 m 2 / g.

11. The battery according to claim 1, wherein The first positive electrode active material is a polycrystalline material and satisfies: The secondary particles have a Dv50 particle size of 6 to 14 μm; and / or, The Dv99 particle size of the secondary particles is <30 μm; and / or, The primary particles have a particle size of 50 to 800 nm; and / or, The BET specific surface area of ​​the first positive electrode active material is 0.8 to 1.2 m 2 / g.

12. The battery according to claim 1, wherein The first positive electrode active material is a polycrystalline material and includes one or more of the following: The Dv50 particle size of the secondary particles is 7 to 13 μm; The Dv99 particle size of secondary particles ranged from 14.2 to 28.8 μm; The Dv99 particle size of secondary particles ranged from 15.4 to 26.7 μm; The particle size of primary particles is 50 to 600 nm; The BET specific surface area of ​​the first positive electrode active material is 0.8 to 1.1 m 2 / g.

13. The battery according to claim 1, wherein The second positive electrode active material is a single crystal or a quasi-single crystal material and satisfies: D of single crystal particles or single crystal-like particles v 50 particle size of 0.2 to 1.6 μm; and / or, D of single crystal particles or single crystal-like particles v 99 particle size is 5.2 to 33.8 μm; and / or, The BET specific surface area of ​​the second positive electrode active material is 11.3 to 14.1 m 2 / g.

14. The battery according to claim 1, wherein The second positive electrode active material is a single crystal or a quasi-single crystal material, and includes one or more of the following: D of single crystal particles or single crystal-like particles v 50 Particle size is 0.25 to 1.49 μm; D of single crystal particles or single crystal-like particles v 99 Particle size is 6.1 to 25.7 μm; The BET specific surface area of ​​the second positive electrode active material is 12 to 13.7 m 2 / g.

15. The battery according to claim 1, wherein The first positive electrode active material has a layered structure; and / or the second positive electrode active material has an olivine structure.

16. The battery according to any one of claims 1 to 15, wherein The first positive electrode active material comprises a core and a coating layer covering the core, wherein the core is a compound Li a Ni b Co c M1 d M2 e O f E g and / or, The second positive electrode active material comprises a core and a coating layer covering the core, wherein the core is a compound Li x H y Mn 1-z Q z P 1-m G m O 4-n D n and / or, The coating layers in the first positive electrode active material and the second positive electrode active material independently include one or more of pyrophosphate, phosphate and carbon.

17. The battery according to claim 16, wherein: The second positive electrode active material includes one or more of the following: The coating layer accounts for 0.5% to 2.2% by mass in the second positive electrode active material; The coating layer accounts for 1% to 1.9% by mass of the second positive electrode active material; The coating layer accounts for 1.2% to 1.5% by mass of the second positive electrode active material; The coating layer in the second positive electrode active material is carbon.

18. An electrical device comprising the battery according to any one of claims 1 to 17.

Citation Information

Patent Citations

  • Security lithium ion battery positive plate as well as preparation method thereof

    CN103811727A

  • Lithium ion battery positive electrode material with adjustable crystalline grain size and preparation method thereof

    CN105118985A

  • Secondary battery and preparation method thereof, and battery module, battery pack and device comprising secondary battery

    CN114730910A

Cited By

  • Battery and electric device

    EP4611068A1

  • Battery and electric device

    WO2024187927A1